ANALISIS PELAYANAN PENGADUAN PUBLIK PADA APLIKASI PORJO (PENGADUAN ONLINE RAKYAT PURWOREJO) DI DINAS KOMUNIKASI, INFORMATIKA, STATISTIK DAN PERSANDIAN KABUPATEN PURWOREJO - Alya Farah Fadhilah; Endang Larasati Setianingsih; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Office of Communication, Informatics, Statistics, and Information Technology of Purworejo Regency has provided a special complaint service for the people of Purworejo through the Porjo Application (People's Online Complaints of Purworejo). However, its implementation has not yet been optimal. This research aims to analyze the complaint service on the Porjo application and the supporting and inhibiting factors in Porjo's service. The research method used is qualitative descriptive with data collection techniques through interviews, observations, and documentation. The theory used in this research is the 5 dimensions theory according to Zeithaml, which includes tangible, reliability, responsiveness, assurance, and empathy. The results of this study indicate that the complaint service on the Porjo application in the Office of Communication, Informatics, Statistics, and Information Technology of Purworejo Regency has implemented these five dimensions. However, in the dimensions of tangible, reliability, and responsiveness, the results have not been optimal due to inadequate facilities, lack of clarity in the implemented standard operating procedures (SOP), and unresponsive personnel in responding to users. Supporting factors in the complaint service of the Porjo application include the community's understanding and the capabilities of the personnel in providing services. Inhibiting factors in the complaint service of the Porjo application include limited human resources, the suboptimal introduction of the service to the public, and unclear SOP of the Porjo application.